Geloofskommunikasie in "n pluriforme wêreld - Dreyer, Yolanda (HTS teologiese studies, 2002)
Communicating faith in a pluriform worldThe pluriformity of the postmodern world presents the church with challenges on different levels. The theological discourse can be based on the pluriformity inherent to biblical material, as well as on the dynamic dialectic of the great variety of theologies in the Bible. The principle of symmetrical communication serves as an example of how pastoral care to a postmodern society can be approached. By making use of narrative communication, pastors facilitate genuine intersubjectivity. Preachers adhere to the principle of symmetrical communication when their sermons are characterized by an authentic spirituality and spiritual growth.